Activity of Actinomycetes Isolated from Mangrove Segara Anakan Cilacap toward Methicillin-resistant Staphylococcus aureus (MRSA) - Ari Asnani; Eva Luviriani; Oedjijono Oedjijono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major health concern because it causes numerous infections in both healthcare facilities and communities. The development of multiresistant against topical antibiotics has caused substantial difficulty in the management of Staphylococcus infection. Thus, this research was aimed to explore indigenous marine Actinomycetes isolated from Segara Anakan Cilacap for anti-MRSA activity. The methods used were screening anti-MRSA activity using agar-block method, production of anti-MRSA extract, extraction of the anti-MRSA extract with ethyl acetate, MIC determination of the ethyl-acetate extract, and species identification based on morphology and 16S rRNA genes. The results indicated that 14 out of 16 Actinomycetes have anti-MRSA activity. Three isolates, which were W-5B, W-5A, and P-7D, showed the highest anti-MRSA activity with the inhibition zone of 2.40 mm, 1.20 mm, and 0.80 mm, respectively. The minimum inhibitory concentration (MIC) of ethyl acetate extract from isolates W-5B, W-5A, and P-7D against MRSA were 2 mg/mL, 4 mg/mL, and 8 mg/mL, respectively. The species identification based on 16S rRNA genes indicated that Actinomycetes W-5B isolate has 92.51% similarity with Streptomyces sp. 2011. The W-5A has 94.69% similarity with Arthrobacter sp. HZ11. The P-7D has 94.79% similarity with Streptomyces clavuligerus strain A-ZN-05. The present study concludes that marine Actinomycetes from sediment mangrove in Segara Anakan Cilacap, Indonesia, has potency as anti-MRSA.